2016
DOI: 10.1177/0003489416629978
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of Functional Swallow After Total Laryngectomy Using High-Resolution Manometry

Abstract: Introduction Understanding of swallowing pressures after total laryngectomy (TL) and what constitutes a “functional” swallow are limited. Mobile structures are altered or removed after TL, with consequent effects on pressure profiles. High-resolution manometry (HRM) can characterize these pressures. Methods Six TL subjects without dysphagia and six controls underwent pharyngeal HRM. Timing and pressure variables for the velopharynx, mesopharynx, and upper esophageal sphincter (UES) were compared. Changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 23 publications
0
17
0
5
Order By: Relevance
“…Another study evaluated six total laryngectomy patients without dysphagia and six control patients, all of them underwent HRM. A decrease in UES pressure was seen in total laryngectomy patients, and the low pressure was due to possible changes in muscle connections at the UES level, especially cricopharyngeal interruption (10) .…”
Section: Discussionmentioning
confidence: 94%
“…Another study evaluated six total laryngectomy patients without dysphagia and six control patients, all of them underwent HRM. A decrease in UES pressure was seen in total laryngectomy patients, and the low pressure was due to possible changes in muscle connections at the UES level, especially cricopharyngeal interruption (10) .…”
Section: Discussionmentioning
confidence: 94%
“…A nivel velofaríngeo, los resultados evidenciaron que los sujetos TL comparados con los controles, exhibieron una mayor duración de la presión velofaríngea (p = 0,012) y una tasa de aumento de la presión velofaríngea más lenta (p = 0,005); mientras que no hubo diferencias en la presión velofaríngea máxima (p = 0,821) y la presión total generada en la velofaringe (p = 0,163). La presión velofaríngea y la duración total de la deglución reflejan la separación de la faringe en conductos distintos para el aire y los alimentos, lo que garantiza el paso exitoso del bolo sin la necesidad de respiración 29 .…”
Section: Primer Autor Actividades Evaluadas Principales Resultadosunclassified
“…Total laryngectomy for laryngeal cancer reportedly has an effect on postoperative pharyngeal pressure and UES dynamics and induces reduced UES pressure, 8 , 13 , 14 prolonged UES relaxation duration, 13 and increased velopharyngeal pressure duration. 8 Cricopharyngeal myotomy can also affect the postoperative swallowing dynamics and result in reduced UES resting pressure 15 , 16 and improved UES relaxation duration during swallowing. 17 , 18 Some studies have reported that no significant change in pharyngeal pressure was observed as a result of cricopharyngeal myotomy for patients with neuromuscular diseases, 15 , 16 , 19 whereas other studies have reported statistically significant increases in peak pharyngeal pressure.…”
Section: Discussionmentioning
confidence: 99%